Implementation of the Drug Abuse Education and Prevention Program of High School and College Students in Southern De Oro Philippines College - Logares, Ruel (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study evaluated the School-Based Drug Abuse Education and Prevention Program of Southern de Oro Philippines College during School Year 2003–2004. Anchored on the concept that coordinated school-based interventions can improve students’ knowledge, attitudes, and behavior toward prohibited drugs, it examined respondents’ socio-economic profiles, family relationships, peer group associations, awareness of common prohibited drugs, perceived reasons for drug use, knowledge of drug effects, and awareness of the school’s prevention program. The study employed descriptive evaluation research using a researcher-made questionnaire and interviews. A total of 250 respondents participated, comprising 125 high school and 125 college students selected through purposive or deliberate sampling. Data were analyzed using frequency, percentage, mean, weighted mean, and Spearman Rank-Order Correlation. Findings showed that most respondents came from low-income households and generally had positive family relationships, although limited communication with parents and feelings of being misunderstood were identified. Peer associations reflected both protective and risky influences, including participation in school activities, support for anti-drug campaigns, alcohol use, peer pressure, and exposure to marijuana. Students were highly aware of common prohibited drugs and their harmful effects. Significant relationships were found between high school and college students’ awareness of common prohibited drugs, perceived reasons for drug use, knowledge of drug effects, and awareness of the school-based prevention program. The study concluded that the program had generally attained its objectives. It recommended strengthening teacher training, curriculum integration, guidance services, student activities, community outreach, school supervision, and future program evaluations. The study supports SDG 3, SDG 4, SDG 16, and SDG 17 through health promotion, preventive education, institutional responsibility, and school-family-community collaboration. Its sustainability impact lies in strengthening long-term educational, public health, institutional, and community systems for preventing drug abuse among students.